Correlation between superficial and deep lymphatic systems using magnetic resonance lymphangiography in breast cancer-related lymphedema: Clinical implications. Issue 6 (June 2020) - Abdelfattah, Usama; Jaimez, Patricia Martinez; Clavero, Juan A.; Bellantonio, Vittoria; Pons, Gemma; Masia, Jaume
Summary: Background: Magnetic resonance lymphangiography (MRL) has increased our knowledge of lymphatic anatomy and lymphedema pathophysiology and improved the efficacy of microsurgical procedures to manage peripheral lymphedema. The aim of this study is to investigate the ability of MRL to detect communications between superficial and deep lymphatic systems in breast cancer-related lymphedema (BRCL) and to investigate whether these communications could preserve lymphatic drainage of the hand. Methods: Between 2008 and 2017 we used MRL imaging in 59 women with BCRL. Lymphedema of the arm and hand was detected in 30 patients while the hand was spared in 29. Using axial and coronal MRL reconstruction images we investigated the existence of any communication between the superficial and deep lymphatic systems. Results: Among the 29 patients with spared hand, MRL revealed that 24 had at least one communicating lymphatic perforator at the wrist region ( p < 0.001). Lymphatic flow at the axilla was clearly visualized in 16 of the 29 patients (55.2%), no perforating lymphatic vessels were detected in the group with lymphedema in the hand (30 patients). Conclusions: Communications between the deep and superficial lymphatic systems at the wrist region in BCRL patients without hand lymphedema should be considered when planning microsurgical lymphatic procedures at the wrist and in postoperative compression therapy.